The earliest settlers of Mesoamerica date back to the late Pleistocene - Stinnesbeck, Wolfgang; Hering, Fabio; Frey, Eberhard; Frank, Norbert; Zell, Patrick (PLOS ONE, 2017)
Preceramic human skeletal remains preserved in submerged caves near Tulum in the Mexican state of Quintana Roo, Mexico, reveal conflicting results regarding 14C dating. Here we use U-series techniques for dating a stalagmite overgrowing the pelvis of a human skeleton discovered in the submerged Chan Hol cave. The oldest closed system U/Th age comes from around 21 mm above the pelvis defining the terminus ante quem for the pelvis to 11311±370 y BP. However, the skeleton might be considerable older, probably as old as 13 ky BP as indicated by the speleothem stable isotope data. The Chan Hol individual confirms a late Pleistocene settling of Mesoamerica and represents one of the oldest human osteological remains in America.